AKUNTABILITAS ADMINISTRASI PERTANAHAN DALAM PENERBITAN SERTIFIKAT - Muhammad Ilham Arisaputra; Muhammad Ashri; Kasman Abdullah; Dian Utami Mas Bakar (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractIn the publishing of certificates of land rights, the government should be able to provide legal certainty. Legal certainty can be achieved if the government’s actions performed accountable. Transparency in land registration is the most important thing in the case of registration of land in order that the maintenance and services procedures run as expected by the public. The effect of the principle of transparency sustainably, it is expected that the information relating to the publishing of a certificate to be accessible to all parties so that if there is information that is considered wrong to do immediate repair. IntisariDalam penerbitan sertifikat hak atas tanah, maka pemerintah harus dapat memberikan kepastian hukum. Kepastian hukum dapat terwujud apabila tindakan pemerintah dilakukan secara akuntabel. Transparansi dalam pendaftaran tanah merupakan hal terpenting dalam hal pendaftaran tanah agar prosedur pengurusan dan pelayanan berjalan seperti yang diharapkan oleh masyarakat. Dengan dilakukannya prinsip transparansi secara berkesinambungan, maka diharapkan informasi yang berkaitan dengan proses hingga penerbitan sertifikat dapat diakses oleh semua pihak sehingga apabila ada informasi yang dianggap keliru segera dapat dilakukan perbaikan.